Analisa Rangkaian Active High Pass Filter Orde 1 dan Orde 2 Topology Sallenkey - Taking, Ahmad; Mulyadi, Mulyadi (Fakultas Teknik dan Ilmu Kelautan, Universitas Hang Tuah, 2025)
A filter is defined as an electrical circuit or network designed to pass or direct alternating current signals generated at certain frequencies while blocking or attenuating all alternating current signals generated at other frequencies. Filters can be classified as analog or digital, passive or active, and audio frequency (AF) or radio frequency (RF) filters. Analog filters are designed to process analog signals, whereas digital filters process analog signals using digital techniques. Depending on the type of elements used in the circuit, filters are categorized into active filters and passive filters. Passive elements include resistors, capacitors, and inductors. Active filters are equipped with transistors or operational amplifiers (op-amps) in addition to resistors and capacitors. The type of element used is determined by the operating frequency range of the circuit. For example, RC filters are generally used for audio or low-frequency operations. In the design of a high-pass filter system, the Sallen-Key topology of first-order and second-order configurations is used, which functions as a building block for implementing higher-order active filters